MANAJEMEN DANA BANK SYARIAH - Nurma Sari (Al-Maslahah : Jurnal Ilmu Syariah, 2016)
The fund given to third party should be well-saved and secured. Therefore, the process of fund pooling and receiving must be based on the rule of Indonesian Bank, DSN, and Islamic bank. Besides, there must be a guarantee of the fund for its safety and cleanliness. Since Islamic bank dominates the use of sharing model, Muāmalah Māliah, for profit and risk,it must provide professional investment management. Moreover, Islamic bank should be careful in selecting investment in order to secure client’s fund. The main purpose of asset management is to maximize profit, minimize risk, and provide sufficient liquidity. Islamic bank has possible risk as well as conventional bank except interest risk as Islamic bank is according to profit and loss sharing. Bank cannot persuade its clients to invest their money without guarantee for security and withdrawal. Thus, bank must consider the risks that can influence the sum of profit: the assessment of budget and planning profit, company investment effectiveness, asset distribution, and strategy asset management implementation. Asset management strategy must be based on the source of fund and investment characteristics.